Study on Strut Effect on Turning Characteristics of LNG Carrier - Bin Mohd Alwi, Mohd Amirul Hamdi; Koto, Jaswar; Zulkarnain, Zulkarnain (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
There are many types of propulsion system used to propel the ship. One of them is podded propulsion system. Up to date, there is still no LNG carrier that was installed with this kind of propulsion system. The idea of installing podded propulsion system onto LNG carrier is till at design and development stage. This paper presents about the study on effect of changing the size of strut of podded propulsor to the turning characteristic of an LNG carrier named Tenaga Satu. The manoeuvring performance of this ship can be predicted by using numerical simulation method. This study is mainly focussing on modifying and developing mathematical model to simulate the turning characteristic of this LNG carrier. Three designs of pod propulsor with different strut length have been made to evaluate the effect to the turning characteristic.